2018
DOI: 10.1016/s1474-4422(18)30025-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of Duchenne muscular dystrophy, part 2: respiratory, cardiac, bone health, and orthopaedic management

Abstract: A coordinated, multidisciplinary approach to care is essential for optimum management of the primary manifestations and secondary complications of Duchenne muscular dystrophy (DMD). Contemporary care has been shaped by the availability of more sensitive diagnostic techniques and the earlier use of therapeutic interventions, which have the potential to improve patients’ duration and quality of life. In part 2 of this update of the DMD care considerations, we present the latest recommendations for respiratory, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
945
4
50

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 790 publications
(1,013 citation statements)
references
References 110 publications
(120 reference statements)
14
945
4
50
Order By: Relevance
“…It should be noted, however, than our study We also evaluated in our study the patient's skeletal system condition after surgery for myelomeningocele. In this group of patients, low bone mass was ac- These drugs are mainly used in disabled patients undergoing glucocorticosteroid treatment who have suffered bone fractures [21].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, than our study We also evaluated in our study the patient's skeletal system condition after surgery for myelomeningocele. In this group of patients, low bone mass was ac- These drugs are mainly used in disabled patients undergoing glucocorticosteroid treatment who have suffered bone fractures [21].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, they suggest some cutoffs to start nocturnal assisted NIV with a backup rate when there are early signs or symptoms of sleep hypoventilation or other sleep-disordered breathing such as abnormal sleep study, FVC < 50% predicted, MIP < 60 cm H 2 O, or awake baseline SpO 2 < 95% or pCO 2 > 45 mm Hg; however, integrating all elements of PFT assessment rather than relying on a single limit value is advisable. Furthermore, daytime NIV should be added when, despite nocturnal ventilation, daytime SpO 2 is < 95%, pCO 2 > 45 mm Hg, or symptoms of awake dyspnea are present [18, 19]. However, real-life studies showed that despite great FVC reduction, many ALS and DMD patients still do not receive NIV at the time suggested by guidelines [20-22].…”
Section: Rationale and Timing For Niv Applicationmentioning
confidence: 99%
“…Moreover, ALS patients during NIV show a decreased pain threshold leading to avoidance of further invasive procedures, increased social restrictions, and raised psychological barriers against transition from NIV to IMV [141]. In case of patient compliance, there are strong recommendations for continuation of NIV up to 24 h according to patient interface preferences [18]. …”
Section: Ethical Dilemmasmentioning
confidence: 99%
“…An anticipatory monitoring approach allows timely initiation of cough assist, nocturnal, and subsequent daytime ventilatory support [23]. In patients with muscular dystrophy type Duchenne, HMV should be discussed and initiated when symptomatic nocturnal hypoventilation or advanced respiratory muscle weakness develops (FVC or maximal inspiratory pressure fall below 50% or 60 cmH 2 O, respectively) [24]. These patients are at risk for daytime ventilatory failure at short or intermediate term [25].…”
Section: Patient Selectionmentioning
confidence: 99%